17x - 6 + 3x - 5 = x + 11 + 4x
20x - 11 = 5x + 11
20x + 1 = 5x + 11
9x = 16x

Question

Asked 2/23/2012 8:02:23 AM

Updated 7/3/2014 10:40:45 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by alfred123 [7/3/2014 10:36:18 AM]

s

trena99|Points 446|

Jackattackk|Points 35|

kikaycore|Points 2460|

debnjerry|Points 27246|

debnjerry|Points 27246|

Question

Asked 2/23/2012 8:02:23 AM

Updated 7/3/2014 10:40:45 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by alfred123 [7/3/2014 10:36:18 AM]

Rating

8

7(x - 3) = 4(x + 5)

7x - 21 = 4x + 20

7x - 4x = 20 + 21

3x = 41

x = 41/3

7x - 21 = 4x + 20

7x - 4x = 20 + 21

3x = 41

x = 41/3

Added 7/3/2014 10:36:23 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/3/2014 3:25:48 PM]

8

x + 6 = x + x

x - x - x = -6

-x = -6

x = 6

x - x - x = -6

-x = -6

x = 6

Added 7/3/2014 10:37:15 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/3/2014 3:26:08 PM]

8

An equation SOMETIMES has one solution.

Added 7/3/2014 10:40:45 AM

This answer has been confirmed as correct and helpful.

36 - 19w = -6w + 41
add -19w
add 6w
add 19w
add -36 **Weegy:** 3. 19w **User:** Solve for x.
9(x - 2) = 18
x = 0
x = 16/9
x = 20/9
x = 4 **Weegy:** 5x-2/50 = 1/10
**User:** Solve for A.
BA + C = D
A = D - B - C
A = (D - C)/B
A = (C - D)/B **Weegy:** ab - 9 = c is the answer. **User:** Score:
Which of the following is the solution set of the given equation?
(x - 3) - 2(x + 6) = -5
{-10}
{-4}
{8} **Weegy:** its -10. wait ill check again **User:** Score:
Solve for B.
A = 3(B + C)
B = (A - C)/3
B = (3A - C)/3
B = (A - 3C)/3 **User:**
5x - 6 = 4x + 8
x = -14
x = -2
x = 2
x = 14 **Weegy:** If 4x + 9 = 17, then x = 2. So 5x would be 10. 10 -1/3 = 9 2/3 **User:** Solve a = for d.
d = ab - c
d = ab + c
d = a/b - c **Weegy:** ab - 9 = c is the answer. **User:** 4y - 6y + 9y = -2
{-2/11}
{-2/7}
{2/7}
{2/11} **Weegy:** y = -2/7 **User:**
7x + 9 = 6x - 5
x = -14
x = -4
x = 4
x = 14 **Weegy:** The equations you stated there are false. If you are looking for the solution to 7x + 9 = 6x - 5x, the solution is -3/2. Source: (More)

Question

Expert Answered

Updated 7/3/2014 10:57:00 AM

5 Answers/Comments

9(x - 2) = 18

9x -18 = 18

9x = 18 + 18

9x = 36

x = 36/9

x = 4

9x -18 = 18

9x = 18 + 18

9x = 36

x = 36/9

x = 4

Added 7/3/2014 10:46:07 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [7/7/2014 10:49:46 AM]

BA + C = D

BA = D - C

A = (D - C)/B

BA = D - C

A = (D - C)/B

Added 7/3/2014 10:47:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [7/7/2014 10:49:57 AM]

A = 3(B + C)

A = 3B + 3C

A - 3C = 3B

B = (A - 3C)/3

A = 3B + 3C

A - 3C = 3B

B = (A - 3C)/3

Added 7/3/2014 10:54:25 AM

This answer has been confirmed as correct and helpful.

5x - 6 = 4x + 8

5x - 4x = 8 + 6

x = 14

5x - 4x = 8 + 6

x = 14

Added 7/3/2014 10:54:51 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [7/7/2014 10:50:14 AM]

The ability of solid rock to flow is called rigidity plasticity firmness flexibility

The ability of solid rock to flow is called PLASTICITY.

Question

Updated 10/14/2015 12:57:19 AM

1 Answer/Comment

The ability of solid rock to flow is called PLASTICITY.

Added 10/14/2015 12:57:19 AM

This answer has been confirmed as correct and helpful.

33,072,934

questions answered

There are no comments.